Análise dos recursos em incubadoras de empresas de base tecnológica - Freire, Clarissa Dourado (2016)
This research aimed to identify and analyze what are the features supported by the incubators of technology-based companies for the incubated companies and analyze what is the importance of these resources for the operation and the incubators and TBCs. As theoretical guidelines were adopted prospects of Resource Based View, which addresses the survival of businesses based on their internal resources and Resource Dependence, which aims to understand the organizational interdependence considering the external environment of organizations. To this end, the triangulation of methods was adopted, with quantitative and qualitative approach, with the use of survey and multi case study. The case study was made with the implementation of semi structured interviews with Supera incubators, Softex and Cinet / Softnet, all in the state of São Paulo and the survey was made the basis of a questionnaire based on the Likert Scale applied to a sample 30 technology-based companies, drawn from a universe of 120 companies that are incubated by the interviewed incubators. For the processing of data were used the descriptive statistics and regression analysis based perspective of total factor productivity, which aims to identify which affects the income of a business and that is not directly related to production factors, with proposing two options, the first being that the resources do not affect the revenue of TBCs and the second is that affect revenue. Even for the case study was made the content analysis. From the survey data it was possible to identify five categories of resources, physical, financial, technological, organizational and human, and further confirm the hypothesis that resources affect the performance of TBCs, and the most representative are the physical resources. It was also observed that the incubators seek ways to provide the resources required for TBCs, are the improvement of its internal resources, as evaluates the resource-based view, are the relationships with other organizations, through the inter-organizational relationships, as recommended by the dependence resources. And TBCs seek in the incubation program a way to deal with the adversities of the environment and the market as well as additional resources.